PENGARUH GAYA KEPEMIMPINAN KARISMATIK, BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KINERJA PENGURUS (Studi Kasus Pengurus Pondok Pesantren Sunan Drajat Paciran Lamongan) - Zaitun Maharani; Abdul Qodir Djaelani; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACKThis study aims to examine and analyze the influence of leadership style, organizational culture and commitment to the performance of the boarding schools of Sunan Drajat Islamic Boarding School both partially and simultaneously. The population in this study amounted to 220 administrators, but was reduced using the Slovin formula to be 69 administrators. Data collection using a questionnaire. Data analysis using SPSS version 14. The sampling technique with census and data testing techniques used in this study include validity test, reliability test, classic assumption test and multiple linear regression analysis and hypothesis testing. The results of the analysis show that the charismatic leadership style and organizational culture have no significant effect on the performance of the management, while the commitment has a significant effect on the performance of the management. And simultaneously the charismatic leadership style, organizational culture and commitment have a positive influence on the performance of the boarding school of Sunan Drajata Paciran Lamongan Islamic Boarding School. Keywords: Charismatic Leadership Style, Organizational Culture, Commitment and Management Performance.